THE EFFECT OF COMPANY SIZE AND FINANCIAL DISTRESS ON AUDITOR SWITCHING USING THE COMPANY GROWTH AS MODERATING VARIABLE AT PROPERTY AND REAL ESTATE COMPANIES IN INDONESIA - Muhammd Yusuf Yusuf; Gunawan Witjaksono; Dwi Sri Dani Afriza; Eka Suci Arista (INQUISITIVE : International Journal of Economic, 2022)
Switching using Company Growth as moderation variables for property and real estate companies listed in Indonesia Stock Exchange in the period of 2015 – 2019. The problem statements being investigated in this study are how is the effect of company size and financial distress on auditor switching and whether company growth could moderate the company size and financial distress on auditor switching for property and real estate companies listed Indonesia Stock Exchange in the period of 2015 – 2019. The study is quantitative research intended to find relationship between variables. The secondary data used in this study is quantitative data obtained from Indonesia Stock Exchange. The sample population of this study covers property and real estate sub-sector companies that publish financial reports in the year of 2015 – 2019. Samples are taken using purposive sampling method during the study period. Based on the completeness of panel data, 105 data were originally available and only 70 data that can be processed. The analytical method used is multiple linear regression which is processed using EViews9. This results of this study indicate that: (1) Company size has a positive effect on Auditor Switching; (2) Financial Distress has no effect on Auditor Switching; (3) Company Size which is moderated by Company Growth influences and increases the effect of Auditor Switching; (4) Financial Distress which is moderated by Company Growth has no effect on Auditor Switching. Recommendation of this study is for the investors to consider all information related to auditor switching prior to the end of auditing exercise before making decision to invest. Keywords: Auditor Switching, Company Size, Financial Distress, Company Growth,